2022
DOI: 10.21203/rs.3.rs-2016158/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fibrocystin/Polyductin releases a C-terminal fragment that translocates into mitochondria and prevents cystogenesis

Abstract: Fibrocystin/Polyductin (FPC) is encoded by PKHD1 which, when mutated, causes autosomal recessive polycystic kidney disease (ARPKD). FPC’s function and its role in cystogenesis are unknown. We describe that endogenous FPC undergoes complex proteolytic processing, generating three small C-terminal fragments (ICDs), one of which (ICD15) contains a novel mitochondrial targeting sequence that directs its translocation into mitochondria. Pkhd1 inactivation leads to aberrant ultrastructural morphology of mitochondria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Interestingly, our cell-based assays showed that disruption of DLG1 leads to over-activation of TAK1 in line with a recent study, showing that Dlg1 deficiency in mouse microglial cells impairs microglial activation and prevents production of inflammatory cytokines [83]. Furthermore, multiple lines of evidence have shown that alterations in ciliary length and inactivation of polycystins can cause profound metabolic rewiring in the kidney, which likely contributes to development of PKD [84][85][86]. Nevertheless, if and how altered ciliary length and composition, as well as dysregulated metabolic, NFκB and TGFβ signalling, contribute to the kidney defects observed in Dlg1 deficient mice and human CAKUT patients with DLG1 mutations awaits further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, our cell-based assays showed that disruption of DLG1 leads to over-activation of TAK1 in line with a recent study, showing that Dlg1 deficiency in mouse microglial cells impairs microglial activation and prevents production of inflammatory cytokines [83]. Furthermore, multiple lines of evidence have shown that alterations in ciliary length and inactivation of polycystins can cause profound metabolic rewiring in the kidney, which likely contributes to development of PKD [84][85][86]. Nevertheless, if and how altered ciliary length and composition, as well as dysregulated metabolic, NFκB and TGFβ signalling, contribute to the kidney defects observed in Dlg1 deficient mice and human CAKUT patients with DLG1 mutations awaits further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…While our studies provide novel information about the nuclear trafficking and function of human and mouse FPC-CTDs, a recent study identified mitochondrial targeting sequences in both mFPC-CTD and hFPC-CTD and demonstrated the trafficking of these proteins into the mitochondria ( Walker et al, 2022 ). These developments imply that understanding both the nuclear and mitochondrial functions of human and mouse FPC-CTDs will be necessary to better define their roles in kidney cystogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…Gene‐edited cultured HEK‐293 cells carrying clinically relevant PKHD1 truncating variants displayed aberrant mitochondrial morphology and increased oxygen consumption and extracellular acidification rates (Chumley et al., 2019). A very recent study identified a shorter ICD fragment (ICD 15 ) that localises to mitochondria via a cryptic mitochondrial targeting sequence (MTS) that overlaps partially with the NLS (Walker et al., 2023). Electron microscopy on renal tubule cells in kidneys from Pkhd1 KO mice revealed mitochondria with significantly decreased surface area, increased roundness and swollen cristae, suggesting a change to the inner mitochondrial membrane.…”
Section: Proteolytic Processing Of Fibrocystinmentioning
confidence: 99%
“…Electron microscopy on renal tubule cells in kidneys from Pkhd1 KO mice revealed mitochondria with significantly decreased surface area, increased roundness and swollen cristae, suggesting a change to the inner mitochondrial membrane. Although mice homozygous for Pkhd1 exon 67 deletion appear healthy (Outeda et al., 2017), this deletion (which removes the MTS) enhanced renal cystogenesis in a Pkd1 ‐defective background (Walker et al., 2023). The FC C‐terminal domain may thus play complex roles in both the nucleus and the mitochondria.…”
Section: Proteolytic Processing Of Fibrocystinmentioning
confidence: 99%